Profil Disolusi Parasetamol Mukoadhesif Menggunakan Kombinasi Polimer Natrium Karboksimetilselulosa dan Gom Arab - Auzal Halim; Riri Hariyani; Maria Dona Octavia (STIFARM Padang, 2010)
Dissolution profiles of 4 formulas of paracetamol mucoadeshif formulas has been done. The test done by using pH 5,8 phosphate buffer as dissolution medium with rowing method, as stated in the Indonesian Pharmacopoeia IV edition. Paracetamol concentrations were measured by UV spectrophotometer at 243 nm. The average dissolution from each formula at 60 minutes are 10.1641%, 15.015%, 11.0631% and 11.8493% respectively. Adhesion test of some mucoadhesive granule adhesion test formulated by using Na-CMC single polymer and a combination of Na-CMC and gum arabic done bioadhesif in vitro assay using rabbit intestinal tissue. The result showed that the combination of Na-CMC polymer and gum Arabic can be used as a polymer bioadhesif because it shows results that meet the requirements of the test bioadhesif.